The Scale, Collections, and Biospecimen Distribution of Grade A Tertiary Hospital Biobanks in China: A National Survey - Chen, Yuanyuan; Sang, Chao; Bian, Zhouliang; Zhang, Yinan; Jiang, Erpeng; Zhou, Xuexun; Chen, Tianlu; Tang, Hongming; Wang, Congrong (Frontiers in Medicine, 2021)
Chinese clinical biobanks were built rapidly in grade A tertiary hospitals. However, the general information of biorepositories in China remained largely unknown. The aim of this study was to investigate the size, collections, biospecimens distribution and other characteristics of Chinese biobanks in grade A tertiary hospitals. In 2018, we launched a national survey among biobank leaders to provide a comprehensive understanding of Chinese grade A tertiary hospital biobanks. A total of 70 biobank managers or directors completed an online questionnaire to collect information about the biorepositories. Nearly 20% of biobanks stored over one million specimens, while almost one-third of biobanks stored 50-200,000 specimens. In general, plasma and serum were the specimens most commonly stored. For the use of collections, biospecimens were most commonly applied by internal clinical departments. Further analyses revealed that the large-scale biobanks were characterized by earlier establishment, more types of specimens in storage and distribution compared with small-scale biobanks. Moreover, specimens in large-scale biobanks were more commonly used for basic research (62.86% vs. 34.29%, P=0.017) and clinical research (57.14% vs. 28.57%, P=0.016). Large-scale biobanks also had more opportunities to cooperate with domestic research institutes (34.29% vs. 5.71%, P=0.003). Our survey revealed diversity in collections, distribution and utilization of biospecimens among Chinese grade A tertiary hospital biobanks. Although the biobanks had relatively large collections, the underutilization of stored biospecimens and lack of sharing could hamper clinical and biological research.